Gridshell em madeira: aspectos teóricos e construtivos - Molina, Julio Cesar [UNESP]; Calil, Carlito; Fé, Anderson Diego Da [UNESP]; Freitas, Ulysses Martins [UNESP]; Morais, Pablo Henrique De [UNESP]; Matos, Gabriela Da Silva [UNESP] (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2019)
Gridshells are light structures that allow the obtention of large spans, as well as the use of a wide variety of architectural shapes. However, in Brazil, there are no records of the construction of this type of structure, neither literature available on this type of structural composition. This paper presents the main theoretical aspects, as well as design and construction details of a gridshell built in wood in real scale. The construction costs are also reported. The structure was built by using a quadrangular flat mesh configuration, formed by double slatted Lyptus wood (Class D40), joined orthogonally, using 6.35 mm diameter screws. The plane mesh (with total dimensions of 9 m x 9 m) was bent until the desired curve was achieved. The system was subsequently locked by diagonal bracing elements. The knowledge obtained through this practical application led to a significant improvement in the original design idea related to controlling the shape of the structure during the building phase and the the optimisation of the executing strategies. The building recommendations presented in this paper will be a contribution to the scarce literature on the subject currently available in Brazil.

As gridshells são estruturas leves, que permitem a obtenção de grandes vãos livres, além de uma ampla variedade de formas arquitetônicas. No entanto, no Brasil, não existem registros da construção desse tipo de estrutura (em caráter permanente) nem muitas informações bibliográficas sobre o seu comportamento estrutural. Neste manuscrito, são apresentados os principais aspectos teóricos, como também os detalhes de projeto e de construção de uma gridshell, construída em madeira, em escala real. Os custos de construção também foram relacionados neste caso. Na confecção da estrutura utilizou-se uma configuração de malha quadrangular plana, formada por ripas duplas de madeira de Lyptus (Classe D40), unidas ortogonalmente entre si por parafusos com diâmetro de 6,35 mm. A malha plana (com dimensões totais de 9 m x 9 m) foi deformada até a obtenção da forma curva desejada e, posteriormente, travada por contraventamentos diagonais. A bagagem de conhecimento adquirida como resultado dessa aplicação prática levou a um aperfeiçoamento significativo da ideia de projeto inicial, relacionada ao controle da forma da estrutura durante as fases de montagem e à otimização das estratégias executivas. As recomendações de construção aqui apresentadas enriquecerão a literatura nacional sobre o assunto tendo-se em vista a carência de textos dessa natureza.
Wood gridshell: theoretical and constructive aspects
Keywords: Wood gridshell; Reticulated structure; Constructive methodology; Gridshell em madeira; Estrutura reticulada; Metodologia construtiva